P11.31.B Pseudotumor Cerebri - a rare paraneoplastic manifestation. (5th September 2022) - Ivan, R; Nistor, L C; Lipan, C G; Mezei, R M; Sirbu, C A
Abstract: Background: Pseudotumor Cerebri (PC) is defined by an elevated intracranial pressure of unidentified cause, associated with normal cerebrospinal fluid (CSF) composition and no cause for hypertension on the neuroimaging evaluations. The symptoms described in association are headache, papilledema, changes in vision, and sometimes tinnitus. Its pathophysiology is far from being elucidated and the mechanisms proposed are multiple. There are some cases described in the literature in which PC is the first manifestation of a systemic neoplasm, most probably due to an abnormal response of the immune system to cancerous growth. We aim to emphasize a possible connection between adenocarcinoma of the lung and PC as the first paraneoplastic manifestation. Material and Methods: We present the case of a 59-year-old patient, female, non-obese, who presented to the hospital for severe headache, blurred vision, tinnitus, and paresthesia on both her upper limbs. On the first evaluation, the usual blood tests showed an increased creatinine level, and the subsequent abdominal echography and CT scan revealed bilateral ureter hydronephrosis, without an obvious obstacle, for which nephrostomies were implanted. On the ophthalmological evaluation bilateral papillary edema was described, although the cerebral CT with angiography and MRI showed no pathological modifications. A lumbar puncture with manometry was performed, that showed a CSF pressure of approximately 500 mmH2O. Results: Following the clinical, imagistic, and biological manifestations, the diagnosis of PC was established. The decision to start the corticotherapy was made, followed by the addition of acetazolamide. Although the treatment tented was not efficient, the neurosurgery team decided that she is not a suitable candidate for a CSF shunting procedure and the ophthalmologist advised against an optic nerve sheath fenestration. The evolution was unfavorable, with the persistence of the symptoms. She underwent extensive investigations, the second cerebral MRI showing a slight dilation of the ventricles. On the thoracic-abdominal-pelvic CT, a pulmonary nodule with a malignant aspect was described, the histopathological results pleading for adenocarcinoma. The decision to excise the lesion was made, but after the surgery, the patient developed a cardiorespiratory arrest, without response to resuscitation. Conclusion: Although there is scarce evidence of PC as a paraneoplastic syndrome, the evolution and investigations results support the possibility of a causal relationship. This is, to our knowledge, the second case of adenocarcinoma of the lung that primarily presents with PC. Further studies must be conducted to understand the underlying pathophysiology of this condition and to develop new treatment possibilities.